Conflicts Management in Natural Resources Use and Environment Protection on the Regional Level - NOVOSELOV, Andrey; POTRAVNII, Ivan; NOVOSELOVA, Irina; GASSIY, Violetta (Journal of Environmental Management and Tourism; Vol 7 No 3 (2016): JEMT Volume VII Issue 3(15) Fall 2016, 2016)
For a long time in the Russian North the biological resources exploitation and a small population density made it possible to avoid conflicts in the nature sphere. Since the end of the XIX century with active industrial developing of Siberia there have been appearing the seats of nature use conflicts. The industrial production development and mining have led to a significant population increasing. Migration, industrial development, environmental damage and natural resources’ use conflicts have become the main factors affecting environmental economics management and social-economic development on the regional level. In the article the issues of Russian Arctic industrial developing accompanied by ecological and economic conflicts are considered. Such conflicts are the results of the investment projects realization on natural resources use. As a rule, the main sides of the ecological and economic conflicts in Arctic are indigenous peoples losing territories of the traditional nature use and subsoil users (gas, oil, diamonds, rare earth metals etc.). The authors offer the conflicts management models which could be used during industrial developing and natural resources’ use in Arctic. The problems of the Arctic environmental sustainable development and conflicts mitigation between target groups within territories of traditional nature use are also considered. The Republic of Sakha (Yakutia)’ experience of the investment industrial projects on natural developing in Arctic zone is analyzed in the paper. The paper aims to develop methods and models of natural resources use, mechanism development of interests’ coordination of target groups during industrial developing of traditional nature use territories on the basis of damage assessment and its compensation. The mentioned models allow resolving socio-economic conflicts in practice; negative processes mitigation in social environment; environmental damage minimizing and subsoil users’ profit maximizing.
Keywords: environmental economics; models of conflicts management; natural resources’ use; regional economics; indigenous peoples